2022
DOI: 10.1002/nafm.10762
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Methods and Survey Designs for Larval Lampreys

Abstract: Knowledge of the biology, distribution, and abundance of lampreys (Petromyzontiformes) is critical to inform conservation actions for native species and to inform control measures for the invasive Sea Lamprey Petromyzon marinus of the Laurentian Great Lakes. Lampreys have complex life cycles that include a freshwater larval stage in which they burrow into substrates consisting of fine sediment and organic matter. The larval stage is frequently targeted in research and monitoring; given this interest, a review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 128 publications
(263 reference statements)
0
18
0
Order By: Relevance
“…Methods to salvage larval lampreys exposed to human‐induced dewatering events have been developed (Lamprey Technical Workgroup 2020). In wadable freshwater habitats, larval lampreys of multiple species are commonly collected using backpack electrofishing (Harvey and Cowx 2003; Moser et al 2007; Clemens et al 2022), and the Lamprey Technical Workgroup has defined best management guidelines for using backpack electrofishing for the purposes of salvaging larval lampreys during either watered or dewatered conditions (Lamprey Technical Workgroup 2020). Electrofishing conducted to salvage larval lampreys when their habitat is dewatered is called “dry shocking” (Lamprey Technical Workgroup 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Methods to salvage larval lampreys exposed to human‐induced dewatering events have been developed (Lamprey Technical Workgroup 2020). In wadable freshwater habitats, larval lampreys of multiple species are commonly collected using backpack electrofishing (Harvey and Cowx 2003; Moser et al 2007; Clemens et al 2022), and the Lamprey Technical Workgroup has defined best management guidelines for using backpack electrofishing for the purposes of salvaging larval lampreys during either watered or dewatered conditions (Lamprey Technical Workgroup 2020). Electrofishing conducted to salvage larval lampreys when their habitat is dewatered is called “dry shocking” (Lamprey Technical Workgroup 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We acknowledge that eDNA sampling has weaknesses that are widely recognized, including for sampling Pacific lamprey (Clemens et al ., 2022). Environmental DNA transport in larger river systems tends to promote detections well downstream of individuals releasing DNA (Pont et al ., 2018; Robinson et al ., 2019), so the downstream terminus of habitat occupancy, if present, is uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…Riaz et al ., 2020). The spatial domain was systematically sampled to ensure even coverage of all potential habitat and to maximize our scope of inference (Clemens et al ., 2022). The majority of samples were collected in a relatively brief period by a small group of biologists and citizen scientists, yet resolved the distribution of a single species across over 10,615 km of potential habitat (itself derived from a 56,168 km stream network).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, results indicated that multiple species frequently co-occur within basins (HUC6), so accurate species identification will be especially important in efforts to characterize the abundance and distribution of lampreys. Since lampreys are most frequently sampled in the field during the larval phase, when they may lack distinguishing morphological features, genetic species identification would improve the accuracy of data collected and would help to advance our understanding of species distributions (Docker et al 2016;Clemens et al 2022). The genetic marker used for DNA barcoding in this study (cyt b) could not distinguish between all nominal lamprey species in California, but molecular identification of different lamprey species (or ecotypes) is likely feasible with higher resolution genomic sequencing techniques.…”
Section: Conclusion and Management Implicationsmentioning
confidence: 99%